2011
DOI: 10.5194/acp-11-7943-2011
|View full text |Cite
|
Sign up to set email alerts
|

Methane flux, vertical gradient and mixing ratio measurements in a tropical forest

Abstract: Abstract. Measurements of CH 4 mixing ratio, vertical gradients and turbulent fluxes were carried out in a tropical forest (Reserva Biológica Cuieiras), about 60 km north of Manaus, Brazil. The methane mixing ratio and flux measurements were performed at a height of 53 m (canopy height 35 m). In addition, vertical CH 4 gradients were measured within the canopy using custom made air samplers at levels of 2, 16 and 36 m above ground. The methane gradients within the canopy reveal that there is a continuous metha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 47 publications
5
33
0
1
Order By: Relevance
“…If noise is truly random, there should not be significant covariance with fluctuations in vertical wind; however this has been observed in other situations (e.g. methane fluxes reported in Querino et al (2011) and Smeets et al (2009)). In the case of PROPHET, we see a less marked increase in cospectral power at the high frequencies, indicating that perhaps noise was less of an issue during this campaign.…”
Section: Cospectral Analysismentioning
confidence: 95%
“…If noise is truly random, there should not be significant covariance with fluctuations in vertical wind; however this has been observed in other situations (e.g. methane fluxes reported in Querino et al (2011) and Smeets et al (2009)). In the case of PROPHET, we see a less marked increase in cospectral power at the high frequencies, indicating that perhaps noise was less of an issue during this campaign.…”
Section: Cospectral Analysismentioning
confidence: 95%
“…Alternatively, one can determine the H 2 O effects in the sampling line before it is deployed in the field (cf. Querino et al, 2011), or the air sample may be dried; however, none of the driers completely removes H 2 O from the air samples. There is always some residual H 2 O left, although it does not necessarily significantly affect the CH 4 fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Further development of the SCIAMACHY IMAP XCH 4 retrieval showed that part of the strong methane signal in the tropics was caused by spectroscopic uncertainties [ Frankenberg et al , , ]. Aerobic CH 4 emissions from living plants were found to be far lower than initially suggested [ Dueck et al , ; Nisbet et al , ; Keppler et al , ; Vigano , ; Querino et al , ] and may be insignificant for the global budget. Recent inversions using SCIAMACHY still show a disagreement between tropical bottom‐up methane emissions inventories and emission estimates derived from satellite observations [ Bergamaschi et al , ], which points to remaining uncertainties in tropical methane emissions, most likely related to underestimated wetland emissions.…”
Section: Introductionmentioning
confidence: 99%